Factors associated with physical activity among Thai women with breast cancer postmastectomy at a university hospital, Thailand: A cross-sectional study - Fuengfa Khobkhun; Piyaporn Wichaidit; Doonyapat Sa-nguanraksa; Surat Phumphuang; Saowaluck Puranasamriddhi; Visnu Lohsiriwat; Watesinee Kaewkhuntee (Scientific Reports)
Abstract The primary treatment for breast cancer patients is surgery which often impacts physical activity (PA). This study aimed to investigate factors associated with the PA level of Thai women with breast cancer after surgical mastectomy at Siriraj Hospital, Thailand. Ninety-three participants completed the questionnaires which included personal information, the Global Physical Activity Questionnaire, perceived benefits, perceived barriers, perceived self-efficacy, interpersonal influence and situational influence, the Thai Body Image Index score, and the Thai Hospital Anxiety and Depression Scale. Data was analysed using descriptive statistics, Chi-square statistics (Odds-Ratio and 95% Confidence Interval) and multiple logistic regression analysis. The study found that post-mastectomy Thai women participated in sufficient PA (2.8 metabolic equivalent of tasks (METs)). It was also found that PA at work was associated with occupation, higher incomes, moderate satisfaction as assessed by the Thai Body Image Index score, and higher levels of anxiety and depression. Participation in recreational activities was associated with older age, higher perceived self-efficacy, and greater interpersonal influence. However, statistically significant associations from the chi-square test did not remain significant after analysis with the multiple logistic regression. By exploring these associations, we can tailor supportive care strategies to address the PA needs of individuals affected by breast cancer which is essential for the development of comprehensive interventions that optimize patient health and well-being throughout the cancer journey.